Cell patterning with mucin biopolymers - Crouzier, T. (2013)
The precise spatial control of cell adhesion to surfaces is an endeavor that has enabled discoveries in cell biology and new possibilities in tissue engineering. The generation of cell-repellent surfaces currently requires advanced chemistry techniques and could be simplified. Here we show that mucins, glycoproteins of high structural and chemical complexity, spontaneously adsorb on hydrophobic substrates to form coatings that prevent the surface adhesion of mammalian epithelial cells, fibroblasts, and myoblasts. These mucin coatings can be patterned with micrometer precision using a microfluidic device, and are stable enough to support myoblast differentiation over seven days. Moreover, our data indicate that the cell-repellent effect is dependent on mucin-associated glycans because their removal results in a loss of effective cell-repulsion. Last, we show that a critical surface density of mucins, which is required to achieve cell-repulsion, is efficiently obtained on hydrophobic surfaces, but not on hydrophilic glass surfaces. However, this limitation can be overcome by coating glass with hydrophobic fluorosilane. We conclude that mucin biopolymers are attractive candidates to control cell adhesion on surfaces.